Peran Guru Dalam Pembelajaran Di Kelas Yayasan Perguruan At-Taufiq SD Swasta - Adinda Julia Putri; Laila Qodri; Muhammad Syah Mahatir; Salwa Nabila Damanik; Salwa Putri Verhan; Sri Solehatun; Inom Nasution (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The aim of this research is to identify the special roles played by teachers in the context of classroom learning at foundation colleges or private elementary schools. The method used in this research is a descriptive research method using qualitative.Data was obtained from interviews, observation and documentation.The teacher's role in classroom learning aims to identify the most effective teaching methods,strategies and approaches in helping students achieve learning goals. The importance of technology integration in classroom learning. Teachers who are able to use technology well can increase the attractiveness of learning, increase access to information, and provide a more interactive learning experience.The use of technology in learning is considered an important aspect of the role of the modern teacher.Effectiveintegration of technology can increase student engagement, facilitate access to information, and stimulate creativity in learning. The importance of technology integration in classroom learning. Teachers who are able to use technology well can increase the attractiveness of learning,increase access to information, and provide a more interactive learning experience. The use of technology in learning is considered an important aspect of the role of the modern teacher. Effective integration of technology can increase student engagement, facilitate access to information, and stimulate creativity in learning.